THE IMPACT OF INCUBATOR & ACCELERATOR STARTUP PROGRAM ON STARTUPPERFORMANCE (STUDY CASE IN INDIGO TELKOM INDONESIA) - Maulida, Hilma
The relationship between the number of startups and the rate of startup failures, emphasizing the need for support mechanisms like incubators and accelerators. These programs offer resources such as co-working space, training, mentorship, business and financial planning, investor networking, and funding. Indigo, a program owned by PT Telkom Indonesia, supports the country's digital startup ecosystem through various stages, including creativity nurturing, incubation/acceleration, business synergy programs, and follow-on funding. However, achieving sustainable business success is challenging, even with participation in such programs. Only a few alumni secure follow-on funding, and some startups fail to make progress despite incubation. Therefore, it is crucial for incubator and accelerator management to assess and refine their programs to better assist early-stage startups in achieving profitability and sustainability. The utilization of incubation and accelerator programs by the Indigo incubator is expected to yield positive effects on the performance of startup businesses. This study aims to determine how respondents perceive the variables of Infrastructure, Management Support, Training & Development, Financial Support, Network, Synergy, and Startup Performance so that they can improve the program that is considered insufficient. In addition, this study also aims to determine the effect between the variables of Infrastructure, Management Support, Training & Development, Financial Support, Network, Synergy on Startup Performance. The research method used in this research is descriptive quantitative method with saturated sample sampling technique and the analysis technique used is descriptive analysis and multivariate SEM PLS. Based on descriptive analysis Indigo Incubator and accelerator program is in good condition, with a value of 78.3%, although there is one variable that is still in the "moderate" category, namely Synergy which obtained a value of 67.2%. Based on the results of hypothesis testing, all incubator and accelerator program variables have a positive effect on startup performance.